Peningkatan Pemahaman Biosekuriti Peternakan Ayam Kampung di Pekarangan Masyarakat Desa Midang Kecamatan Gunung Sari Lombok Barat - Suryadi, Muh. Aidil Fitriyan Fadjar; Septian, I Gede Nano; Anwar, Khairil; Saedi, M. Ridwam (Jurnal Gema Ngabdi, 2025)
The native chicken farming sector in Midang Village, Gunung Sari District, West Lombok, mostly still uses an extensive system, which poses a high risk of disease spread. The lack of biosecurity implementation in these farms has an impact on the high mortality rate of chickens and low productivity. The purpose of this community service is to increase farmers' understanding of the importance of stable biosecurity to prevent the spread of disease and increase livestock productivity. This activity is carried out through socialization, counseling, and practical training on biosecurity, including making simple disinfectants, stable sanitation, and traffic control on the farm. As a result, farmers began to implement better biosecurity measures, which are expected to reduce disease risk and improve farmer welfare. This program contributes to ensuring the sustainability of the native chicken farming business in Midang Village by educating farmers about the importance of implementing biosecurity. Keywords: Native chicken, Biosecurity, House Sanitation